2021
DOI: 10.1136/jitc-2021-003495
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled biological and chronological aging of neutrophils in cancer promotes tumor progression

Abstract: BackgroundBeyond their fundamental role in homeostasis and host defense, neutrophilic granulocytes (neutrophils) are increasingly recognized to contribute to the pathogenesis of malignant tumors. Recently, aging of mature neutrophils in the systemic circulation has been identified to be critical for these immune cells to properly unfold their homeostatic and anti-infectious functional properties. The role of neutrophil aging in cancer remains largely obscure.MethodsEmploying advanced in vivo microscopy techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Recently, it has been shown that uncoupled biological and chronological aging of neutrophils contributes to the progression of cancer and promotes advanced stages of malignant disease ( 82 ). Using a mouse squamous cell carcinoma cell line (SCC VII), we showed a noteworthy positive association between the RNA expression levels of formyl peptide receptor 1 (FPR1), an established marker gene of neutrophils, and of C-X-C motif chemokine receptor 4 (CXCR4), whose gene product increases during neutrophil aging on the surface of these immune cells, with higher tumor stages ( 83 , 84 ). Activation of the NLRP3 inflammasome in perivascular macrophages by tumor-released Damage-associated molecular patterns (DAMPs) such as S100A8/9 induce the synthesis of inflammatory mediators that upregulate adhesion and signaling molecules on the surface of microvascular endothelial cells, in turn promoting the trafficking of aged neutrophils to the perivascular space ( 84 ).…”
Section: Neutrophils: Cells With a Multitude Of Rolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that uncoupled biological and chronological aging of neutrophils contributes to the progression of cancer and promotes advanced stages of malignant disease ( 82 ). Using a mouse squamous cell carcinoma cell line (SCC VII), we showed a noteworthy positive association between the RNA expression levels of formyl peptide receptor 1 (FPR1), an established marker gene of neutrophils, and of C-X-C motif chemokine receptor 4 (CXCR4), whose gene product increases during neutrophil aging on the surface of these immune cells, with higher tumor stages ( 83 , 84 ). Activation of the NLRP3 inflammasome in perivascular macrophages by tumor-released Damage-associated molecular patterns (DAMPs) such as S100A8/9 induce the synthesis of inflammatory mediators that upregulate adhesion and signaling molecules on the surface of microvascular endothelial cells, in turn promoting the trafficking of aged neutrophils to the perivascular space ( 84 ).…”
Section: Neutrophils: Cells With a Multitude Of Rolesmentioning
confidence: 99%
“…Activation of the NLRP3 inflammasome in perivascular macrophages by tumor-released Damage-associated molecular patterns (DAMPs) such as S100A8/9 induce the synthesis of inflammatory mediators that upregulate adhesion and signaling molecules on the surface of microvascular endothelial cells, in turn promoting the trafficking of aged neutrophils to the perivascular space ( 84 ). Following antibody-mediated depletion of aged neutrophils, a significant decrease in the growth of tumors was observed in experimental HNSCC ( 84 ). Aged neutrophils are related to a more pro-tumorigenic state.…”
Section: Neutrophils: Cells With a Multitude Of Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that large eccentric plaques and plaques with high inflammatory activity intensively accumulate CXCR4-expressing cells from the systemic circulation [ 31 , 32 ]. In addition, it is possible that as polyvascular atherosclerosis progresses, there is an increase in the systemic circulation of signaling molecules that trigger excessive and accelerated neutrophil aging, something that has been recently described as occurring in malignant tumors and HIV infections [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of TANs, the interplay between CCs and neutrophils was mainly investigated through the analysis of patient samples [ 16 ] and in vivo models [ 17 , 18 ]. These approaches led for instance to the development of innovative strategies to impair neutrophil migration and recruitment to the tumor microenvironment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%